ON NEW SPECIES STILESIA ALII N.SP. (CESTODA-THYSANOSOMIDAE, FUHRMANN, 1907) FROM CAPRA HIRCUS AT HASNABAD (JALNA), INDIA - BORDE, S.N.; SHINDE, G.B. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1999)
This paper deals with the description of a new species of genus Stilesia (Railliet, 1893) Stilesia alii n.sp. differs from earlier characters such as scolex large, round or oval, nature segments small or squarish, testes medium, round 11 in number (i.e. 5 + 6 = 11, 6+5 = 11); cirrus pouch medium, situated in the anterior half of the segment; ovary large, oval, a single mass; open marginally, the par uterine organ big, oval two in each gravid segment.